The Role of Vitamin B12 in Stroke: An Overlooked Association - Dr Shreya Nigoskar, Salender Singh, Dr Swarnima Singh (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: This study aimed to evaluate the relationship between vitamin B12 levelsand acute cerebral stroke.